Development of adp-glo™ assay for entamoeba histolytica choline kinase activity measurement - Hassan, Mohammad Shafiq (Universiti Sains Malaysia, 2016)
Entamoeba histolytica choline kinase (EhCK) is the first enzyme in the biosynthesis of phosphatidylcholine (PtdCho). Phosphatidylcholine (PtdCho) is one of the major glycerophospholipids in E. histolytica membrane. Therefore, EhCK inhibition has been suggested as a potential anti-amoebic strategy. Currently, pyruvate kinase-lactate dehydrogenase (PK-LDH) coupled assay is one of the enzyme assays used to measure EhCK activity. A high consumption of enzyme protein, large volume of assay reagents, and long experimental duration in PK-LDH coupled assay, suggesting a new method to measure EhCK activity is required. This study reports the development of ADP-Glo™ assay as a new method for the measurement of EhCK activity. E. coli BL21 that had been transformed with pGEX-RB-GST-EhCK plasmid was cultured in 100 mL of LB broth supplemented with 100 pg of ampicillin and induced with a final concentration of 1 mM of IPTG, for 16 hours at 27°C for the expression of GST-EhCK. The EhCK expressed was then purified by using GST*bind resin. Two types of EhCK was co-purified which were GST-tagged EhCK and untagged EhCK with a molecular weight of ~60 kDa and 40 kDa, respectively. To determine the linear range of EhCK reaction using ADP-Glo™ assay, the EhCK reaction was performed with different kinase reaction times. It was found that the ADP-Glo assay was linear until 60 minutes and 20 minutes for reaction with Mg2 and Mn2+ ion as cofactors, respectively. The EhCK activity measurement using ADPmeasure Gio™ assay was subsequently performed based on the assay condition and kinase reaction time that represent linear range of EhCK reaction. The activities measured using ADP-Glo™ assay were then compared to the activities obtained from PK-LDH coupled assay. The independent t-test results showed a significant difference (p<0.05) in the Vmax values obtained from the two methods, for choline in the presence of Mg2+ ion, where the ADP-Glo™ assay had a higher value (0.712 U/mg) than PK-LDH coupled assay (0.144 U/mg). A significant difference in the Kni values was obtained for choline (p<0.05) in the presence of Mn2+ ion as cofactor, where ADP-Glo™ assay had lower Km values (0.227 mM) compared to PK-LDH coupled assay (0.655 mM). Other kinetic parameters showed no significant difference between the two methods. In conclusion, this study had successfully developed a new enzyme assay for measurement of EhCK activity by using ADP-Glo™ assay.